Methodological Principles of Interdisciplinary Research : The Integrated Study of the Image in Social Networks (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
This text examines the basic methodological principles of interdisciplinary studies to discuss disciplinary scientific collaboration strategies around the integrated study of the image. It explores three specific areas of research: the principle of definition of the specialized positioning of interdisciplinary research and its pertinence with image study scenarios; the principle of disciplinary integration, and the use of sociodemographic variables in the study of online media and social networks and the principle of conflict reconciliation applied to the comprehensive study of the image on Instagram, Facebook and Twitter.